A Structured Benefit-Risk Assessment to Evaluate a Combination of Olanzapine and Samidorphan for the Treatment of Schizophrenia and Bipolar I Disorder. (April 2022) - Roy, Brittany D.; McDonnell, David; Yu, Bei; Graham, Christine; Jiang, Ying; Yagoda, Sergey; Bhupathi, Vasudev; DiPetrillo, Lauren
Abstract: Background: A combination of olanzapine and samidorphan (OLZ/SAM) that provides the efficacy of olanzapine while mitigating weight gain was recently approved by the FDA for the treatment of schizophrenia and bipolar I disorder. To improve communication of the OLZ/SAM benefit-risk profile, a structured framework was utilized. Methods: The Benefit-Risk Action Team framework was used to evaluate OLZ/SAM, with analyses completed for each pivotal study. ENLIGHTEN-1 evaluated antipsychotic efficacy and safety. ENLIGHTEN-2 evaluated the weight profile of OLZ/SAM vs olanzapine. Benefit-risk outcomes were selected based on study outcome parameters, known risks of olanzapine and samidorphan, and public health importance. A subset of opioid antagonist risks was not assessed due to clinical trial exclusions; however, they were factored into the overall evaluation. Risk differences and confidence intervals were analyzed. Results: In ENLIGHTEN-1, OLZ/SAM had a lower risk of psychiatric discontinuation and nonresponse to treatment compared with placebo; higher risks of hyperprolactinemia, weight gain (≥7%), sedation, and worsening of fasting triglycerides and glucose, and no difference for fasting total and LDL cholesterol, neutropenia, orthostatic hypotension, and movement disorders. In ENLIGHTEN-2, OLZ/SAM had reduced risks of weight gain and waist circumference increase compared to olanzapine along with similar risks of relapse and psychiatric discontinuation and no difference in metabolic worsening, neutropenia, hyperprolactinemia, orthostatic hypotension, sedation, and movement disorders. Discussion: Based on this assessment, OLZ/SAM has comparable efficacy and a safety profile consistent with olanzapine, with reduced weight gain. A structured approach to assessing the benefit-risk profile of a product facilitates transparent evaluation and communication. Funding: Alkermes, Inc.